Terrestrial heat flow and its role in petroleum geology; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Osipova E. N. Elizaveta Nikolaevna; Ivanov I. V.; Smirnov V. A.; Abramova R. N. Raisa Nikolaevna (Petroleum Geology. Current Exploration and Extraction Methods, 2015)
Title screen